2010
DOI: 10.1002/pon.1853
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the attitudes and behaviors of oncologists regarding the truthful disclosure of information to patients with advanced and incurable cancer

Abstract: Objective: To evaluate the attitudes of the European Oncologists to information disclosure to patients with advanced cancer, their self-reported behaviors, and the factors that influence both attitudes and behaviors.Methods: ESMO members were invited to complete an online questionnaire to evaluate both attitudes and clinical behaviors relating to the disclosure of information to patients with advanced cancer. Data were analyzed to evaluate demographic, educational and social factors influencing attitudes and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 88 publications
0
16
0
3
Order By: Relevance
“…7,8,16,18,19 However, a recent study showed that oncologists are often unwilling, unable, or uncomfortable with honestly disclosing and discussing information regarding diagnosis and prognosis with patients with advanced disease. 20 In addition, many HCPs avoid discussing the topic or withhold information. 21 Furthermore, HCPs tend to underestimate patients' need for information and overestimate patients' understanding of their prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,16,18,19 However, a recent study showed that oncologists are often unwilling, unable, or uncomfortable with honestly disclosing and discussing information regarding diagnosis and prognosis with patients with advanced disease. 20 In addition, many HCPs avoid discussing the topic or withhold information. 21 Furthermore, HCPs tend to underestimate patients' need for information and overestimate patients' understanding of their prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Education and training has been suggested by Rogg et al 19 and Cherny20 as methods to change physicians’ attitudes towards disclosure of prognostic information. Friedrichsen et al 7 found that when healthcare staff were educated about communicating transition to end-of-life care, they expressed frustration because economic constraints made it difficult to incorporate their new knowledge into their clinical work.…”
Section: Discussionmentioning
confidence: 99%
“…This study, published in 2010, 9 highlighted the importance of education and the institutional culture of care within individual hospitals as major factors influencing oncologist's practices of disclosure and communication (box 2).…”
Section: Improving the Provision Of Pc For Patients With Cancer By Onmentioning
confidence: 99%
“…This has been a challenging project on many levels: intellectually, scientifically and even philosophically. It has involved multiple incarnations, extensive and rigorous field testing and Box 2 Major findings from the ESMO communication survey 9 Based on responses from 298 oncologists across all regions of Europe, the study indicated that individual clinicians generally display a range of behaviours, including non-disclosive as well as disclosive behaviours, depending on the dynamics of individual interactions between oncologist and specific patient. Although regional cultural norms influence oncologists' attitudes towards disclosure and, indirectly, their self reported behaviours, the impact is influenced by other factors: in particular, perceived institutional professional norms, the degree of training in breaking bad news and the frequency of exposure to requests by family members to withhold information from the patient.…”
Section: Promoting Honest and Clear Communication Regarding The Capacmentioning
confidence: 99%